Utilizing sensors networks to develop a smart and context-aware solution for people with disabilities at the workplace (design and implementation) - Ghassan Kbar; Ahmad Al-Daraiseh; Syed Hammad Mian; Mustufa Haider Abidi (International Journal of Distributed Sensor Networks)
The developments and improvements in human–computer interaction and information and communication technologies have resulted in innovative assistive technology (AT) solutions for the people with disabilities (PWDs). Although, there have been many new ideas and technologies for assisting the PWDs, still very few of them have considered the workplace environment. Therefore, there is a need to develop a comprehensive universal AT solution that can maximize the PWDs productivity at work. In this work, an AT and smart context-aware solution has been developed to assist the PWDs at the workplace. This has been achieved through the designing and the implementation of a smart unified interface to guide and assist the PWDs. A wireless sensor network has been employed in this context-aware smart solution in order to track and determine user’s location. The unified interface is adaptive and includes four modules that are smart helping, smart communication, smart editor, and auto emergency response. A proper AT process and technological design considerations have been adopted to achieve a comprehensive, universal, adaptive, and context-aware solution.